Weak convergence theorems for a countable family of strict pseudocontractions in banach spaces - Suthep Suantai (2018)
We investigate the convergence of Mann-type iterative scheme for a countable family of strict pseudocontractions in a uniformly convex Banach space with the Fréchet differentiable norm. Our results improve and extend the results obtained by Marino-Xu, Zhou, Osilike-Udomene, Zhang-Guo and the corresponding results. We also point out that the condition given by Chidume-Shahzad (2010) is not satisfied in a real Hilbert space. We show that their results still are true under a new condition. Copyright © 2010 Prasit Cholamjiak and Suthep Suantai.